Geophysical Applications In Mapping The Subsurface Structure Of Archaeological Site At Lembah Bujang, Kedah, Malaysia - Sapiai, Sarmiza Mohamed (2011)

(untitled)
Lembah Bujang is one of Peninsular Malaysia's most important areas for archaeology as excavations in this area have revealed many traces of Malaysia's protohistory. The site is one of the oldest known place human civilization activities in the Peninsula. The aim of this study is to map and understand the subsurface structure of the survey area which is one of the archaeologically interesting areas. The specific areas of study are Sungai Batu and Sungai Bujang. Geophysical methods are used because it is non-destructive and non-invasive.